2008 30th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2008
DOI: 10.1109/iembs.2008.4649769
|View full text |Cite
|
Sign up to set email alerts
|

From spikes to EEG: Integrated multichannel and selective acquisition of neuropotentials

Abstract: Abstract-Electrical signals recorded from the brain cover a wide range of amplitudes, frequencies, and spatial scales, from spikes and local field potentials (LFP) inside the brain to electrocorticograms (ECoG) and electroencepalograms (EEG) outside. Each of these signal modalities represent different aspects of neural dynamics that can be combined to infer brain state and function in a broader context. We present a 16-channel interface circuit fabricated in a 0.5 µm CMOS process for the selective acquisition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
(12 reference statements)
0
8
0
Order By: Relevance
“…However the acquiesced signal always presents distortion components -harmonic distortion. Although, researchers are trying to develop systems capable of amplifying and reduce harmonics in EEG signals [27], power consumption of devices bring issues according to the distortion caused by the power supply [28].…”
Section: Signal Analysismentioning
confidence: 99%
“…However the acquiesced signal always presents distortion components -harmonic distortion. Although, researchers are trying to develop systems capable of amplifying and reduce harmonics in EEG signals [27], power consumption of devices bring issues according to the distortion caused by the power supply [28].…”
Section: Signal Analysismentioning
confidence: 99%
“…Today analog-to-digital converters (ADCs) are increasingly being integrated into time-multiplexed low-power highresolution biosensor applications, such as wearable and implantable biomedical systems [1][2][3]. While the required bandwidth is generally relaxed, the required resolution is, on the other hand, more stringent and varies from 12 to 16 bits, depending on each specific application.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the application, different signal amplitudes and frequency bands have to be taken into consideration for signal processing and signal evaluation [1]. In recent studies, an increased use of electrocorticographical (ECoG) recordings is observed.…”
Section: Introductionmentioning
confidence: 99%